Penerapan Metode Imla’ Istima`I Untuk Meningkatkan Keterampilan Menulis (Maharatul Kitabah) Bahasa Arab Siswi Kelas VIII Shofiyah Di SMP Qur’an Darul Fattah Bandar Lampung (Al Mitsali : Jurnal Penelitian dan Pendidikan Bahasa Arab, 2024)
This research is based on the lack of application of appropriate learning methods to support the learning process of Arabic writing skills, a lack of effective time in learning Arabic writing skills, a lack of training for students to develop Arabic writing skills, and a lack of knowledge of students in writing Arabic. Arabic writing is good and correct. The formulation of the problem in this study is "Can the application of the Imla 'Istima`i method improve the Arabic writing skills (maharatul kitabah) of students of class VIII Shofiyah even semester of SMP Qur`an Darul Fattah?". While the purpose of this study is "to describe the effect of the application of the Imla` Istima`i method in improving the Arabic writing skills (maharatul kitabah) of students of class VIII Shofiyah even semester of SMP Qur`an Darul Fattah". Therefore, researchers undertake alternative solutions using the imla` istimai` method because it can help students hone their writing skills properly and correctly. The research subjects were 23 students of class VIII Shofiyah Qur`an Darul Fattah Bandar Lampung, and this research was conducted in 2 cycles with 3 meetings in each cycle. This is evidenced by the increase in the percentage of results from cycle I to cycle II, in the first cycle it obtained an average value of 78.04 and in the second cycle it obtained an average value of 80.39. So the increase in cycle I to cycle II reaches 2.35%. Based on the results of the research that has been done, it is concluded that the imla` istimai` method can improve the writing skills of Shofiyah class VIII students of SMP Qur`an Darul Fattah in Bandar Lampung. What researchers do in this method is to convey how to write the imla` properly and correctly, by providing example sentences, translating Arabic texts and rewriting the contents of the Arabic text